2021
DOI: 10.21037/tp-20-256
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell function assays in the diagnosis of infection in pediatric liver transplantation: an open-labeled, two center prospective cohort study

Abstract: Background: Limited studies have been performed in assessment of immune status of pediatric liver transplants (PLTs). We conducted this study to evaluate Cylex immune cell function assay in diagnosis of infection and its potential clinical application in Chinese infant PLTs. Methods:In this prospective cohort study, 227 infant PLTs from two medical centers were enrolled, and 216 completed the study. Cylex ATP values were measured before and after liver transplantation (LT) at week 1, 2, 3, 4, 8, 12 and 24 resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Our study revealed a significant correlation between CD4 + iATP concentration and the counts of white blood cells and neutrophils in sepsis patients, consistent with the findings reported by Naderi et al 26 , 41 However, a previous study indicated no association between iATP levels and white blood cell counts. 32 Therefore, further research is needed to determine whether CD4+ iATP levels can effectively reflect systemic inflammation and innate immune responses.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our study revealed a significant correlation between CD4 + iATP concentration and the counts of white blood cells and neutrophils in sepsis patients, consistent with the findings reported by Naderi et al 26 , 41 However, a previous study indicated no association between iATP levels and white blood cell counts. 32 Therefore, further research is needed to determine whether CD4+ iATP levels can effectively reflect systemic inflammation and innate immune responses.…”
Section: Discussionsupporting
confidence: 93%
“…Our study, along with other relevant reports, supports the notion that monitoring the concentrations of iATP produced by CD4 + T cells could be valuable in distinguishing between hypoimmune and hyperimmune states. 26 This approach may aid in identifying patients at risk of infection or death, adjusting immunosuppressive agents according to CD4 + iATP content can help reduce mortality and infection in transplant patients, ultimately enhancing the effectiveness of immunotherapy interventions. By assessing CD4 + iATP levels, clinicians may be able to stratify patients and tailor immunomodulatory treatments accordingly, optimizing their response to therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Measuring the activity levels of CD4 + T lymphocytes in the peripheral blood of patients to early identify the potential risks of rejection and infection in organ transplant recipients [21]. In sepsis, some studies have reported signi cantly higher sATP CD4 of survivors compared to non-survivors within the rst day of ICU admission [14,32]. These contrasting results indicate the complexity of sATP CD4 and its potential implications in different disease states.…”
Section: Discussionmentioning
confidence: 99%